Neurological complications observed in dengue patients during the 2023–2024 outbreak: experience of the J. M. Cullen Hospital, Santa Fe, Argentina (SigMe, 2025)
During the 2023–2024 dengue epidemic outbreak in Argentina, neurological manifestations associated with the infection were observed with increasing frequency, which prompted this study at Hospital J.M. Cullen, Santa Fe. A retrospective, descriptive analysis was conducted on patients who were hospitalized with confirmed dengue and neurological complications between November 2023 and May 2024. Eighteen cases were analyzed. Complications were central in 77.8 % and peripheral in 22.2 % of the cases. The most frequent were Guillain-Barré syndrome, seizures, and ischemic stroke. Fifty per cent (50%) of the patients required intensive care. The mortality rate was 5.6 %, and one-third required rehabilitation. The findings are consistent with regional studies and show that dengue can present with neurological involvement of varying severity.
Keywords: Neurological manifestations; Dengue; Guillain-Barré síndrome; Encephalitis; Argentina